2021
DOI: 10.2967/jnumed.121.262250
|View full text |Cite
|
Sign up to set email alerts
|

The added value of 18F-FDG PET/CT compared to 68Ga-PSMA PET/CT in patients with castration-resistant prostate cancer

Abstract: Purpose:The 68 Ga-prostate specific membrane antigen (PSMA) positron emission tomography/computed tomography (PET/CT) is a commonly used imaging modality in prostate cancers. However, few studies have compared the diagnostic efficiency between 68 Ga-PSMA and 18 F-FDG PET/CT and evaluated whether a heterogeneous metabolic phenotype (especially PSMA-FDG+ lesions) exists in patients with castration-resistant prostate cancer (CRPC). We determined the added value of 18 F-FDG PET/CT compared to 68 Ga-PSMA PET/CT in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
(20 reference statements)
2
8
0
Order By: Relevance
“…There is a slow proliferation and low glucose metabolism of early PCa, and the role of 18 F-FDG in the primary stage of PCa is limited [19,20]. However, 18 F-FDG may play an important role in castration-resistant PCa and some heterogeneous tumor phenotypes with low or no expression of PSMA [21,22]. Here, we compared the new PSMA tracer 18 F-PSMA-1007 and the most commonly used clinical tracer 18 F-FDG in PET/CT scanning of the same patient.…”
Section: Discussionmentioning
confidence: 99%
“…There is a slow proliferation and low glucose metabolism of early PCa, and the role of 18 F-FDG in the primary stage of PCa is limited [19,20]. However, 18 F-FDG may play an important role in castration-resistant PCa and some heterogeneous tumor phenotypes with low or no expression of PSMA [21,22]. Here, we compared the new PSMA tracer 18 F-PSMA-1007 and the most commonly used clinical tracer 18 F-FDG in PET/CT scanning of the same patient.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study comparing PSMA PET with FDG PET in mCRPC found 18 F‐DCFPyL PET detected more lesions than FDG PET, but there was only 22% concordance between 18 F‐DCFPyL and FDG PET 175 . A different study in CRPC patients found higher Gleason scores and PSA levels may predict development of FDG‐positive disease 176 …”
Section: Nuclear Theranostics: Lessons Learned and Future Directionsmentioning
confidence: 98%
“…For example, Chen et al, in a study of 56 patients, found that 23.2% had at least 1 discordant lesion and that prostate serum antigen (PSA) and Gleason score were both higher in these patients (Fig. 1) (14).…”
Section: Patient Selectionmentioning
confidence: 99%